51-5x=-63+x

Simple and best practice solution for 51-5x=-63+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 51-5x=-63+x equation:


Simplifying
51 + -5x = -63 + x

Solving
51 + -5x = -63 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
51 + -5x + -1x = -63 + x + -1x

Combine like terms: -5x + -1x = -6x
51 + -6x = -63 + x + -1x

Combine like terms: x + -1x = 0
51 + -6x = -63 + 0
51 + -6x = -63

Add '-51' to each side of the equation.
51 + -51 + -6x = -63 + -51

Combine like terms: 51 + -51 = 0
0 + -6x = -63 + -51
-6x = -63 + -51

Combine like terms: -63 + -51 = -114
-6x = -114

Divide each side by '-6'.
x = 19

Simplifying
x = 19

See similar equations:

| 0,25(4x-3)=3-x | | -17-6z=-9(7z+8) | | 0,1(4x-3)=3-x | | -3+7n=39forn | | -33=-3n-4n | | 2/3x+1/4=5/6 | | 87=2x-5 | | 10x*y-50000=0 | | 13-2t=4 | | 28000=20000+0.3x | | Y=20000+0.3x | | 8=4p+12 | | 6x^2-3=4x | | 6x^2-3=3x | | 2-3(x-1)=-2-2(1-3x) | | 3(2x-5)=33 | | 1-(3-8x)=2(2x+4) | | a+68=-72 | | 4-8x+2x=6+5(x+4) | | 2y^3-18y+3y^2-27=0 | | x/8=17 | | 5.51+4.3a=67 | | 8+4x=2x+2+24 | | 68-f=-72 | | 0.074d-3.4=0.707 | | 12x+12=36+6x | | f-68=-72 | | 20x+60=x^2-8x | | -0.1x-0.45=-0.77 | | -x^2+12x+60=0 | | -10=-x | | 2+12.5v=0.55 |

Equations solver categories